Generation 3 PAMAM dendrimer TAMRA conjugates containing precise dye/dendrimer ratios. (September 2015) - Manono, Janet; Dougherty, Casey A.; Jones, Kirsten; DeMuth, Joshua; Holl, Mark M.Banaszak; DiMaggio, Stassi
Graphical abstract: Abstract: The synthesis, isolation, and characterization of generation 3 poly(amidoamine) (G3 PAMAM) dendrimer containing precise ratios of 5-carboxytetramethylrhodamine succinimidyl ester (TAMRA) dye ( n  = 1–3) per polymer particle are reported. Stochastic conjugation of TAMRA dye to the dendrimer was followed by separation into precise dye-polymer ratios using rp-HPLC. The isolated materials were characterized by rp-UPLC, MALDI-TOF-MS, and 1 H NMR spectroscopy, UV–vis, and fluorescence spectroscopies.